2016
DOI: 10.1016/j.ijantimicag.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

The G-quadruplex-forming aptamer AS1411 potently inhibits HIV-1 attachment to the host cell

Abstract: HighlightsThe G-quadruplex-forming aptamer AS1411 strongly inhibits HIV-1 infection.AS1411 is non-toxic to the host cell at antiviral concentrations.AS1411 blocks viral attachment to the host cell.AS1411 binds cell-surface-expressed nucleolin, a putative HIV-1 co-receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…AS1411 was reported to have the ability to bind NCL [28, 29]. In this study, we demonstrated that NCL was over-expressed in glioma cells and tissues.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…AS1411 was reported to have the ability to bind NCL [28, 29]. In this study, we demonstrated that NCL was over-expressed in glioma cells and tissues.…”
Section: Discussionmentioning
confidence: 52%
“…Because of the multifunctional nature of NCL, it has been proposed that many secondary targets are affected following treatment with AS1411 [34]. NCL is higher expressed in tumor cells than in normal cells [3536], besides, NCL expresses in cell membrane, cytoplasm and nucleus in tumor cells while only within nucleus in normal cells [29, 37], AS1411 binds NCL on external surface of the cell and then is internalized [9]. Expressing only nucleus NCL, NHA is weakly respond to AS1411 mainly due to the limited internalization and interaction with NCL.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, aptamers have been considered an alternative or adjuvant to the chemical antiviral agents in cART to overcome these limitations. To date, highly specific, nucleic acid-based aptamers that target various parts of HIV-1 genomes, HIV-1 proteins (including HIV-1 protease (PR), reverse transcriptase (RT), nucleocapsid, gp120, and Gag) and cellular proteins (nucleolin, CD4 or CCR5) have been isolated and shown to effectively suppress viral replication to apply in HIV therapy [5,25,26,27] (Figure 2). …”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…The major molecular target of AS1411 is NCL. Perrone et al tested whether the aptamer AS1411 was able to interfere with HIV-1 cellular entry using different HIV-1 strains, host cells and at various times post-infection [26]. The results demonstrated that AS1411 efficiently inhibited HIV-1 attachment/entry into the host cell in the absence of cytotoxicity at the tested doses.…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…This leads to biological effects including reduction of bcl‐2 expression, disturbance of the repair processes of DNA damage, and induction of tumor suppressor gene expression . AS1411, as an anticancer agent is now completed two phase clinical . Therefore, the combination of chemotherapy, PTT, and biotherapy was applied to improve the efficacy of tumor treatments.…”
Section: Introductionmentioning
confidence: 99%